A Sub-GHz multimode digital polar transmitter for 802.11ah and NB-IoT applications. (February 2023) - Li, Tong; Yin, Yun; Liu, Yangzi; Xu, Hongtao; Min, Hao
Abstract: This paper presents a sub-GHz multimode efficiency-enhanced digital polar transmitter for IoT applications. The Class-G technique and wideband matching network are introduced in the switched-capacitor digital power amplifier (DPA) to enhance the 6 dB back-off efficiency and achieve 550–950 MHz wide frequency coverage. The digital baseband processing module is flexibly reconfigurable to support both 802.11ah and NB-IoT protocols. Moreover, the canonic signed digit (CSD) coding and first-order hold (FOH) interpolation techniques are employed to reduce power consumption. Implemented in 55 nm CMOS technology, this digital transmitter (DTX) achieves 23.7dBm peak power, 44.6% peak PAE and 36.1% PAE at 6 dB power back-off at 800 MHz. The DTX obtains 16.7dBm average output power, 33.9% average PAE with −28.8 dB EVM for the 2 MHz 64QAM 802.11ah signal, and 18.6dBm average output power, 37.5% average PAE with −19.8 dB EVM for the 12-subcarrier 180 kHz NB-IoT signal.